Development of a single-phase thermosiphon for cold collection and storage of radiative cooling. (1st November 2017) - Zhao, Dongliang; Martini, Christine Elizabeth; Jiang, Siyu; Ma, Yaoguang; Zhai, Yao; Tan, Gang; Yin, Xiaobo; Yang, Ronggui
Highlights: A single-phase thermosiphon is proposed for cold collection and storage of radiative cooling. Thermal performance and fluid flow characteristics of the thermosiphon are explored. The feasibility of using single-phase thermosiphon for cold collection and storage of radiative cooling is demonstrated. Parameters that affect thermosiphon performance are experimentally investigated. Abstract: A single-phase thermosiphon is developed for cold collection and storage of radiative cooling. Compared to the conventional nocturnal radiative cooling systems that use an electric pump to drive the heat transfer fluid, the proposed single-phase thermosiphon uses the buoyancy force to drive heat transfer fluid. This solution does not require electricity, therefore improving the net gain of the radiative cooling system. A single-phase thermosiphon was built, which consists of a flat panel, a cold collection tank, a water return tube, and a water distribution tank. Considering that outdoor radiative cooling flux is constantly changing (i.e. uncontrollable), an indoor testing facility was developed to provide a controllable cooling flux (comparable to a radiative cooling flux of 100 W/m 2 ) for the evaluation of thermosiphon performance. The testing apparatus is a chilled aluminum flat plate that has a controlled air gap separation relative to the flat panel surface of the thermosiphon to emulate radiative cooling. With an average of 105 W/m 2 cooling flux, the 18 liters of water in the thermosiphon was cooled to an average temperature of 12.5 °C from an initial temperature of 22.2 °C in 2 h, with a cold collection efficiency of 96.8%. The results obtained have demonstrated the feasibility of using a single-phase thermosiphon for cold collection and storage of radiative cooling. Additionally, the effects of the thermosiphon operation conditions, such as tilt angle of the flat panel, initial water temperature, and cooling energy flux, on the performance have been experimentally investigated. Modular design of the single-phase thermosiphon gives flexibility for its scalability. A radiative cooling system with multiple thermosiphon modules is expected to play an important role in cooling buildings and power plant condensers.